First record of the alien polychaete Naineris setosa (Scolecida; Orbiniidae) in Tyrrhenian Sea (Western Mediterranean). Issue 1 (December 2016) - Atzori, Giulia; López, Eduardo; Addis, Pierantonio; Sabatini, Andrea; Cabiddu, Serenella
Abstract During a survey in Santa Gilla, a Tyrrhenian lagoon located in southern Sardinia, several specimens of the alien polychaeteNaineris setosa were found. 1) A brief description of the specimens is presented; they possess the rounded prostomium and the crenulated capillary chaetae typical of the genus, but they are characterized by the absolute lacking of uncini or subuluncini in thoracic neuropodia, which is unique trait withinNaineris; 2) some environmental characteristics of the collection site are measured; 3) the description and the distribution of the specimens are also provided.